Peringatan Hari Murka Tuhan (Zefanya 2:1-3) dan Relevansinya Terhadap Orang Percaya Masa Kini - Trinitas Nuryani Dakhi; Hetri Anida Siregar; Valen Ardison Tamba; Grecet Inovitria Merliana (Jurnal Silih Asuh : Teologi dan Misi, 2024)
In responding to the warning of the day of God's wrath, Christians believe that the warning of the day of God's wrath is a decree of the law that will actually occur at His second coming. The topic of commemoration about the Day of the Lord nowadays is rarely discussed either in sermons or in other gatherings. For this reason, this topic has become an important topic of discussion and must be explored again among believers. The aim of this writing is to analyze the form of commemoration of the day of God's wrath and its relevance for believers today. The method we use in this writing is a deductive (descriptive) method by collecting various sources as references, namely journals, books and articles related to this topic.